Shakespeare, Brecht, and the Intercultural Sign - Tatlow, Antony (Book collections on Project MUSE., 2001)
Examines Asian staging of Western canonical theater, particularly Shakespeare's plays, arguing that intercultural performance questions the settled assumptions we bring to our interpretations of familiar texts.